Pengaruh Waktu Reaksi pada Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Terumbu Karang Melalui Proses Hidrotermal - Dani Pradana; Yelmida Azis; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Coral reefs in Indonesia have a good predicate of around 65%, while damaged coral reefs are around 35%. The damaged coral reefs have not been used optimally, whereas coral reefs have a high content of calcium carbonate which is as much as 78.81%, so that damaged coral reefs can be used as raw material for the synthesis of Hydroxyapatite (HAp). Hydroxyapatite is a bioceramics that can be used as a bone and dental grafting material, catalyst or adsorbent. This study aims to synthesize hydroxyapatite through the formation of Precipitated Calcium Carbonate (PCC) from coral reefs. The research procedure begins with the coral reefs calcination process to form CaO which is then made into PCC with the carbonation method. PCC as a source of calcium was synthesized into hydroxyapatite using a hydrothermal process at 140oC with various reaction times 11, 12, 13, 14, 15, 16, and 17 hours. Hydroxyapatite from the synthesis results is analyzed by X-ray Diffraction (XRD). The results of XRD analysis showed the formation of hydroxyapatite compounds from an angle of 2θ which corresponds to the data (ICDD 01-072-1243). Hydroxyapatite synthesized at a reaction time of 15 hours gave the best results with a hexagonal crystal structure and a crystal size of 49.81141 nm.Keywords : carbonation, hydrothermal, PCC, reaction time.